Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.25002/tji.2018.965
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Viral Infections and Allergic Inflammation in Asthmatic Patients on Immunotherapy

Abstract: Introduction: The prevalence of allergic asthma are increasing, and the clinical outcome and risk factors of immunotherapy in the treatment of allergy have not been well established. Especially, the impact of viral infection on cytokines in allergic inflammation has yet to be established. This study aimed to determine serum IL-3, IL-11 and IgE levels and blood eosinophil and neutrophil counts during a one-year follow up in patients with allergic asthma on immunotherapy and those on anti-asthmatic drugs only, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…Besides SLIT in these patients demonstrated to be safe and well tolerated. In another prospective study, the effect of an influenza virus infection on standard immunological parameters during one year course of SCIT in asthmatic patients was investigated 58 . The authors found that the presence of influenza‐like symptoms during SCIT had not affected standard biochemical and hematological parameters (eg, eosinophil and neutrophil counts, total IgE).…”
Section: Discussionmentioning
confidence: 99%
“…Besides SLIT in these patients demonstrated to be safe and well tolerated. In another prospective study, the effect of an influenza virus infection on standard immunological parameters during one year course of SCIT in asthmatic patients was investigated 58 . The authors found that the presence of influenza‐like symptoms during SCIT had not affected standard biochemical and hematological parameters (eg, eosinophil and neutrophil counts, total IgE).…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective and comparative clinical study, Ahmetaji et al found no significant difference in the efficacy or in the improvement of symptoms of allergic asthma patients under subcutaneous allergen‐specific immunotherapy with or without symptomatic influenza, nor in the standard chemical and hematology parameters and different cytokines during a one‐year follow‐up 32 . These preliminary data suggest that SCIT in influenza‐infected patients was safe and well‐tolerated.…”
Section: Introductionmentioning
confidence: 99%
“…In their prospective and comparative clinical study, Ahmetaji et al [18] found no significant difference in effectiveness or symptom improvement in patients with allergic asthma using SCIT with or without influenza-like viral infections. The laboratory chemical and hematological standard parameters and various cytokines during treatment and 1 year follow-up were also not different [18]. These preliminary data suggest that SCIT is safe and well-tolerated in patients with influenza virus infection.…”
Section: Position Papermentioning
confidence: 97%